Integration of the Influence of Green Knowledge and Green Competency in Improving Innovative Work Behavior with the Role of Leader Support Mediation in the Garment Industry - Joko Purnomo; Nur Wening; Ifah Rofiqoh; Tri Gunarsih; Sujoko; Yudan Hermawan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the integration of the influence of green knowledge and green competency in improving innovative work behavior (IWB) with the role of leader support mediation in the garment industry in Semarang Regency. The research approach used is quantitative with an explanatory research design. Data was collected through the distribution of questionnaires to 200 garment industry employees selected using purposive sampling techniques. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the help of SmartPLS. The results of the study show that green knowledge, green competence, and leader support have a positive and significant effect on innovative work behavior. In addition, green knowledge and green competency have also been proven to have a significant effect on leader support. The leader support variable has the most dominant influence on innovative work behavior. The results of the mediation test showed that leader support was able to mediate the relationship between green knowledge and green competency to innovative work behavior partially. The value of the determination coefficient (R²) indicates that the model has strong explanatory ability, while the SRMR value indicates that the research model has a good fit. This research provides the implication that the improvement of innovative employee behavior in the garment industry is not only dependent on environmental knowledge and competence, but is also strongly influenced by the support of leaders. Therefore, organizations need to develop integrated strategies in increasing green knowledge, green competence, and strengthening leadership roles to encourage sustainable innovation.